Mowing of Carex brevicuspis (Cyperaceae) improves food quality for herbivorous geese in Dongting Lake: the potential mechanisms - Wu, Tao; Xia, Le; Pan, Baihan; Zou, Yeai; Li, Feng; Xie, Yonghong; Wang, Shengze; Li, Zhuoya (Frontiers in Plant Science, 2025)
The operation of the Three Gorges Dam has altered the hydrological regime of Dongting Lake, leading to earlier water level recession and premature lake bed exposure. The hydrological shift has accelerated the early development of Carex spp.-dominated meadows, resulting in phenological mismatches between Carex brevicuspis (the primary food source for herbivorous geese) and the arrival of herbivorous geese. This mismatch has reduced suitable food resources for these geese during their wintering period. This study aimed to assess how mowing treatments mitigate this mismatch by improving the quality of C. brevicuspis. During the 2023/2024 wintering season, we studied the effects of mowing treatments on C. brevicuspis and the underlying mechanisms. Three treatments were applied: complete mowing (CM; stubble height < 0.3 cm), stubble mowing (SM; stubble height 15 cm), and no mowing (CK). The results showed that mowing treatments significantly increased leaf moisture and nitrogen content, reduced crude fiber content, and thereby increased the quality and food utilization rates by herbivorous geese. Additionally, mowing increased the quality of C. brevicuspis by stimulating compensatory growth responses, which relies on the resources of the belowground bud banks mechanisms. However, mowing treatments also significantly decreased plant height, density, aboveground biomass, and the biomass of belowground bud banks, which potentially impairs the long-term recovery and sustainability of plant. Therefore, while targeted mowing can effectively improve the food quality for herbivorous geese during wintering, careful consideration of the management of mowing frequency and intensity are essential to maintain balance between the wetland vegetation recovery and the sustainable food supply for herbivorous geese.